Property Frames - Jonathan Remy Nash; Stephaine M. Stern (Washington University Law Review, 2010)
Property law confronts circumstances where owners' excessive perceptions of their ownership rights impose social costs, frustrate policy goals, and hamper the very institutions meant to support private property. Groundbreaking research in cognitive framing suggests an answer to the question of how to selectively attenuate (or strengthen) ownership perceptions. In a novel application of this research, we contend that property law may “set frames” for individual owners. Specifically, we hypothesize that framing property as bundles of rights and forewarning of limitations weakens perceptions of ownership and decreases resistance to subsequent restrictions. We conducted experiments to evaluate these claims and found that both bundle-of-rights/discrete-asset framing and forewarning framing affect perceptions of ownership, rights infringement, valuation, and satisfaction. Our study shows that “layering” both of these conditions (bundle framing and forewarning) have a stronger, synergistic impact than the sum of each effect alone. The potential applications of this research to property theory are numerous. Legislators, judges, and regulatory agencies craft legal measures that respond to, or even capitalize on, strong, preexisting frames of citizen-owners. These institutional players also endeavor to limit spillovers and other social harms by reframing property as a limited set of use rights in areas of law including pollution rights, intellectual property, and common interest communities.
Keywords: Property rights; Social costs; Social cognitive theory